PENGEMBANGAN DESAIN KOTAK PAKET BERBASIS DATA ANTROPOMETRI - Rossi S Wahyuni; Yuyun Yuniar Rohmatin; Mei Raharja; Ayu Tasya Annisa (Jurnal Ilmiah Teknik, 2024)
A package box is a container or place that functions to make it easier for the package courier to put the package by requiring some certain body posture movements so that the package can be placed firmly in place. Anthropometry is a set of numerical data related to the physical characteristics of the human body, size, shape and strength and the application of the data to the handling of design problems. The purpose of this study is to identify the posture of use and develop a package box design based on anthropometric data of the posture of the initial package box user when placing and picking up packages. The results of the calculation of anthropometric data based on the 5th, 50th, and 95th percentile precenttility values for the development of the package box design were obtained that the length of the Package Box (95th) was 50.5085 ≈ 51 cm, the width of the Package Box (5th) was 30.6067 ≈ 31 cm, while the height of the package box (50 years) was 136.77 ≈ 137 cm. The comparison of the dimensions of the initial package box is 50 x 50 x 70 cm, while the result of the development of the design of the package box is 51 x 31 x 137 cm. The position of opening the reference package box is carried out with the position of hunched shoulders and the position of reaching the hands down when placing and picking up the package, while the position of the user of the developed package box when placing the package and the position of reaching the forward hand when placing and picking up the package with an upright posture